Fourth Generation Phosphorus-Containing Dendrimers: Prospective Drug and Gene Delivery Carrier - V. Dzmitruk; A. Shakhbazau; D. Shcharbin; A. Chernov; V. Kulchitsky; A.-M. Caminade; J.-P. Majoral; M. Talabaev; M. Bryszewska; E. Pedziwiatr-Werbicka; M. Potapnev; S. Kosmacheva; et al. (MDPI AG, 2011)
Research concerning new targeting delivery systems for pharmacologically active molecules and genetic material is of great importance. The aim of the present study was to investigate the potential of fourth generation (P4) cationic phosphorus-containing dendrimers to bind fluorescent probe 8-anilino-1-naphthalenesulfonate (ANS), anti-neoplastic drug cisplatin, anti-HIV siRNA siP24 and its capability to deliver green fluorescent protein gene (pGFP) into cells. The interaction between P4 and ANS (as the model drug) was investigated. The binding constant and the number of binding centers per one molecule of P4 were determined. In addition, the dendriplex between P4 and anti-HIV siRNA siP24 was characterized using circular dichroism, fluorescence polarization and zeta-potential methods; the average hydrodynamic diameter of the dendriplex was calculated using zeta-size measurements. The efficiency of transfection of pGFP using P4 was determined in HEK293 cells and human mesenchymal stem cells, and the cytotoxicity of the P4-pGFP dendriplex was studied. Furthermore, enhancement of the toxic action of the anti-neoplastic drug cisplatin by P4 dendrimers was estimated. Based on the results, the fourth generation cationic phosphorus-containing dendrimers seem to be a good drug and gene delivery carrier candidate.